"No Maths, No Physics (So I Spray My Bars with Lyrics)": Rap/Music Therapy with Young Men at a Young Offender Institution. (June 2014) - Short, Helen
This paper describes work undertaken at a young offender institution, focusing on the therapeutic use of improvised or 'freestyle' and original rap. In particular it uses material and analysis pertaining to two individuals who formed part of a slow open group for outpatients detained in the main prison. A background to the work sets the scene. Next the author details the role of this specific form of therapy within the institution addressing the aims of the work and the background of the clients. The main body of the paper examines the nature of this work from a psychodynamic perspective, incorporating concepts of Klein, Winnicott, Holmes and Bowlby. This relates to the setting, client group and the use of rap as a therapeutic intervention, with focus on original rap lyric-writing and the stylistic and cultural connotations of the genre. Original lyrics and therapeutic techniques specific to clients are drawn upon and discussed.